Role of Spiritual Health on Job Stress among Nurses A Cross-sectional Study in an Educational Hospitals of Qazvin City - Sima Rafiei; Mohammad Zakaria Kiaiei; pejman sadeghi; zahra rahmati (Tehran University of Medical Sciences, 2019)
Background: One of the main important principles of human health is spirituality which its promotion could lead to an effective control of work related stress; can be considered in nurses' job performance and assurance of their physical and mental health as a crucial factor. This study aimed to explore the effect of spiritual health on job stress among nurses employed in a training hospital affiliated to Qazvin University of Medical Sciences in 2017. Materials and Methods: This was a descriptive-cross sectional one conducted on 220 nurses at Velayat hospital in Qazvin city. Data gathering was performed using two standard questionnaires including spiritual health and nurseschr('39') job stress. Data analysis was carried out with SPSS22 using descriptive statistical methods, Pearson Correlation Coefficient and multivariate regression analysis at a significance level of P < 0.05. Results: The mean score of spiritual health and job stress assessed at a moderate level 70.5±5.2 and77.5±2.3, respectively. Spiritual health in both religious and intrinsic dimensions, gender, job history and type of employment were statistically related to job stress (p<0.05). Furthermore, multiple regression analysis revealed these variables predict 25% of job stress variation. Conclusion: Due to the important role of spiritual health on job stress among nurses, strengthen this dimension of health through acknowledging them about its potential effects on physical and mental health and ultimately on successful job performance recommended.